Sources and identification of microplastics in soils - Weixin Fan; Chunsheng Qiu; Qian Qu; Xiangang Hu; Li Mu; Ziwei Gao; Xin Tang (Elsevier, 2023)
Large-scale production, rapid consumption, insufficient recovery and management, and slow degradation lead to a large accumulation of plastic waste and microplastics. Microplastics are characterized as stable, small, and having a large specific surface area and strong hydrophobicity. They are carriers of many hydrophobic organic pollutants, heavy metals, pathogenic bacteria and drug resistance genes. Worldwide, microplastic pollution in soils has attracted much attention. The progress and perspectives in the separation and detection of soil microplastics deserve a comprehensive review and discussion. Here, the sources and distributions of microplastics in soil from the use of agricultural plastic film, sludge recycling, long-term application of organic fertilizer, surface runoff, and sewage irrigation are summarized. Physical separation methods such as density separation, electrostatic separation, oil extraction and pressurized liquid extraction, and chemical extraction methods such as acid digestion, alkaline digestion, hydrogen peroxide and Fenton reagent oxidation, and enzymatic hydrolysis for soil microplastics are reviewed. Futhermore, the detection technologies of soil microplastics through microscopy, spectroscopy, mass spectrometry, thermogravimetric analysis, differential scanning calorimetry, X-ray photoelectron spectroscopy and nuclear magnetic resonance are reviewed. Finally, the perspectives are put forward from understanding the impacts of microplastics on soil functions and health, developing source control and environmental remediation technology, investigating low-cost and rapid separation and extraction methods that preserve the characteristics of microplastics, strengthen the degree of automation to avoid artificial operation error, and establish the standard methods for isolating, extracting, identifying, and quantifying microplastics in soils. This review serves as a technical reference for rapid identification of soil microplastics and builds the foundation for scientific assessment of the ecological and human environmental risks of soil microplastics.